APLIKASI PENJADWALAN DAN ESTIMASI PRODUKSI PADA PT. INDOMETIC - Rantung, Stella Ester; Sutrisno, Tri; Herwindiati, Dyah Erny (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
PT. Indometic is a company that producing stainlees steel product which is they need to use a lot of machine for producing their product. Campbell Dudek Smith is one of schedule method that will help this company to determine the optimum job sequences that can minimize makespan. Recently, this company faces some problem such as production lateness because they don’t have any scheduling system and they don’t have any forecast system for their product selling. Time Series method is a series of data that have some forecast method that can help this company to know how many product can be selling for the future time. The result from forecast method will be processed with Economic Order Quantity to find how many material that company needs to producing their product. Some  products from PT. Indometic that will going to get scheduling and forecasting are deep fryer, bread mixer and hotsnack. For scheduling the optimum sequence are hotsnack, bread mixer and deep fryer. And then for forecasting deep fryer product is 14 pieces, hotsnack  9 pieces and bread mixer is 1 piece